A novel quartz-crystal microbalance humidity sensor based on solution-processible indium oxide quantum dots. Issue 66 (26th November 2019) - Kan, Hao; Li, Min; Li, Hui; Li, Chong; Zhou, Jian; Fu, Chen; Luo, Jingting; Fu, Yongqing
Abstract : A high-performance QCM humidity sensor was prepared based on In2 O3 QDs with a high specific surface area. Abstract : Having a large surface area, like the quantum confinement effect also caused by the nano-level size of quantum dots (QDs), creates fantastic potential for humidity sensing. A high concentration of surface adsorption sites initiates an increased response. Porosity between QDs allows fast water vapor penetration and outflow. Here, a quartz-crystal microbalance (QCM) humidity sensor was prepared using indium oxide (In2 O3 ) QDs, synthesized via a solvothermal method. After the In2 O3 QDs were directly spin-coated onto the QCM, an annealing process removed organic long chains and exposed more moisture adsorption sites on the surfaces of the QDs. The annealed QCM humidity sensor exhibited high sensitivity (56.3 Hz per %RH at 86.3% RH), with a fast response/recovery time (14 s/16 s). Long carbon chains were broken down, and hydrogen-bonded hydroxyl groups were chemisorbed to the QDs. The chemical reaction was reduced by these chemisorbed hydrogen-bonded hydroxyl groups. Mass change was mostly caused by fast multilayer physisorption. Thus, the transducer can effectively and precisely monitor the moisture from a person's breath. In2 O3 QD-modified QCM sensors demonstrate promising humidity-sensing applications in daily life.